Quantification and Spectral Interference Studies of Selected Weak Chromophore Molecules Using ATR-FTIR Spectroscopy with Regression Tools - Lee, Jia Ying; Teoh, Amira Teoh Binti Mohd Shukri; Lokesh, Bontha Venkata Subrahmanya; Shrivastava, Preeti Bala (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Weak chromophore molecules present challenges in analytical method development for routine quality control testing. This study focuses on three such molecules: favipiravir and molnupiravir, antiviral drugs repurposed for COVID-19 treatment, and etidronate disodium, used for osteoporosis and multiple myeloma. Existing analytical methods face limitations due to their non-chromophore structures. Objectives: To address this, we developed three non-destructive ATR-FTIR (Attenuated Total Reflectance Fourier Transform Infrared) spectroscopic methods for purity assessment. Materials and Methods: Infrared spectra were scanned in the full IR region (4000-667 cm⁻¹), with calibration curves generated via TQ Analyst Pro software using partial least squares regression. The fingerprint regions (1393-1062 cm⁻¹) for favipiravir; Near-IR regions (1700-667 cm⁻¹) for molnupiravir and etidronate disodium) demonstrated excellent linearity (r² ≈ 0.9998-1.000). Results: The residual mean standard errors of calibration was <0.0025 for three active molecules, and intra-day/inter-day precision had relative standard deviations less than 5% after validation as per ICH guidelines. Conclusion: Interference studies confirmed that no spectral overlaps with inactive ingredients after comparing both placebos with and without all three above drugs, allowing potential application of this method for routine analysis of the formulation. These methods offer a sensitive, specific, and accurate and alternative method for quantitative analysis of weak chromophore molecules.
Keywords: Attenuated total reflectance infrared spectroscopy; Etidronate; Favipiravir; Molnupiravir; Quantification; Validation